Sinomenine Hydrochloride Ameliorates Fish Foodborne Enteritis via α7nAchR-Mediated Anti-Inflammatory Effect Whilst Altering Microbiota Composition - Xie, Jiayuan; Li, Ming; Ye, Weidong; Shan, Junwei; Zhao, Xuyang; Duan, You; Liu, Yuhang; Unger, Bruno Hamish; Cheng, Yingyin; Zhang, Wanting; Wu, Nan; Xia, Xiao-Qin (Frontiers in Immunology, 2021)
Foodborne intestinal inflammation is a major health and welfare issue in aquaculture. To prevent enteritis, various additives have been incorporated into the fish diet. Considering anti-inflammatory immune regulation, an effective natural compound could potentially treat or prevent intestinal inflammation. Our previous study has revealed galantamine’s effect on soybean induced enteritis (SBMIE) and has highlighted the possible role of the cholinergic anti-inflammatory pathway in the fish gut. To further activate the intestinal cholinergic related anti-inflammatory function, α7nAchR signaling was considered. In this study, sinomenine, a typical agonist of α7nAChR in mammals, was tested to treat fish foodborne enteritis via its potential anti-inflammation effect using the zebrafish foodborne enteritis model. After sinomenine’s dietary inclusion, results suggested that there was an alleviation of intestinal inflammation at a pathological level. This outcome was demonstrated through the improved morphology of intestinal villi. At a molecular level, SN suppressed inflammatory cytokines’ expression (especially for tnf-α) and upregulated anti-inflammation related functions (indicated by expression of il-10, il-22 and foxp3a). To systematically understand sinomenine’s intestinal effect on SBMIE, transcriptomic analysis was done on the SBMIE adult fish model. DEGs (sinomenine vs soybean meal groups) were enriched in GO terms related to the negative regulation of lymphocyte/leukocyte activation and alpha-beta T cell proliferation, as well as the regulation of lymphocyte migration. The KEGG pathways for glycolysis and insulin signaling indicated metabolic adjustments of α7nAchR mediated anti-inflammatory effect. To demonstrate the immune cells’ response, in the SBMIE larva model inflammatory gatherings of neutrophils, macrophages, and lymphocytes caused by soybean meal could be relieved significantly with the inclusion of sinomenine. This was consistent within the sinomenine group as CD4+ or Foxp3+ lymphocytes were found with a higher proportion at the base of mucosal folds, which may suggest the Treg population. Echoing, the sinomenine group’s 16s sequencing result, there were fewer enteritis related TM7, Sphingomonas and Shigella, but more Cetobacterium, which were related to glucose metabolism. Our findings indicate that sinomenine hydrochloride could be important in the prevention of fish foodborne enteritis at both immune and microbiota levels.